PENINGKATAN PEMAHAMAN KONSEP PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL PEMBELAJARAN WORDSQUARE PADA SISWA KELAS III SD NEGERI TANJUNGHARJO NANGGULAN KULONPROGO - Septi Erliasari; AL Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research was to improve the comprehension of using the model learning word square on the subject Civic Education third grade students State Elementary School Tanjungharjo. This research use class action research (PTK). The subject of the research was third class student, while its object was comprehension of concept Civic Education. The data gained of this research from observation result, test and documentation. The research result show, model learning word square can increase comprehension of concept Civic Education. It shows an increased outcomes pre-action around 66,80, on the first cycle increased to 72,88 and the second cycle increased to 80,57. The number of students have reached on pre-action as many as 11 students or 42,30%. First cycle increased to 15 students or 57,69%. At second cycle increasing significantly to 21 of the 26 students or 80,76%. The research result show that the use of learning word square can increase comprehension of concept Civic Education on the students State Elementary School Tanjungharjo, Nanggulan, Kulon Progo.